Nebivolol Acts as a S-Nitrosoglutathione Reductase Inhibitor: A New Mechanism of Action. (September 2016) - Jiang, Hong; Polhemus, David J.; Islam, Kazi N.; Torregrossa, Ashley C.; Li, Zhen; Potts, Amy; Lefer, David J.; Bryan, Nathan S.
Background and Purpose: Published data on nebivolol reveal selective β1 adrenergic selectively along with novel nitric oxide (NO)-dependent vasodilatory properties. However, the exact molecular mechanism is unknown. Protein S-nitrosylation constitutes a large part of the ubiquitous influence of NO on cellular signal transduction and is involved in a number of human diseases. More recently, protein denitrosylation has been shown to play a major role in controlling cellular S -nitrosylation (SNO). Several enzymes have been reported to catalyze the reduction of SNOs and are viewed as candidate denitrosylases. One of the first described is known as S -nitrosoglutathione reductase (GSNOR). Importantly, GSNOR has been shown to play a role in regulating SNO signaling downstream of the β-adrenergic receptor and is therefore operative in cellular signal transduction. Pharmacological inhibition or genetic deletion of GSNOR leads to enhanced vasodilation and characteristic of known effects of nebivolol. Structurally, nebivolol is similar to known inhibitors of GSNOR. Therefore, we hypothesize that some of the known effects of nebivolol may occur through this mechanism. Experimental Approach: Using cell culture systems, tissue organ bath, and intact animal models, we report that nebivolol treatment leads to a dose-dependent accumulation of nitrosothiols in cells, and this is associated with an enhanced vasodilation by S -nitrosoglutathione. Key Results: These data suggest a new mechanism of action of nebivolol that may explain in part the reported NO activity. Conclusions and Implications: Because exogenous mediators of protein SNO or denitrosylation can substantially affect the development or progression of disease, this may call for new utility of nebivolol.